Not by sight [large type] - Breslin, Kate (Thorndike Press large print Christian historical fiction, 2015)
With all of Britain's attention on the front lines of WWI, Jack Benningham, dashing heir to the Earl of Stonebrooke, has declared himself a conscientious objector. Wealthy young suffragette Grace Mabry hands Jack a white feather of cowardice at a posh masquerade ball -- never anticipating the danger set into motion by her actions.